The impact of money on output in Czech Republic and Romania - Simionescu, Mihaela; Balcerzak, Adam P.; Bilan, Yuriy; Kotásková, Anna (Journal of Business Economics and Management, 2018)
The problem of relationship between output and money has become again a subject of special interests of economists after the most recent global financial crisis and monetary stabilization policies applied by central banks of almost all developed economies. In this context, the main aim of this paper is to assess the relation between GDP and the most important monetary variables in two countries: Romania and Czech Republic over the period of 1995:Q1 – 2015:Q4. The choice of these economies was deliberate. The selected countries are different from the viewpoint of rate and results of transformation from the centrally planned to market economy, which have influenced their current economic environment stability. Czech Republic is currently classified as middle or even developed country, whereas Romania is still considered as a developing economy. Thus, differences between these two countries make them interesting in the case of comparative studies. In the empirical part of our research the vector error correction models (VECM) were applied. The main findings of the article are the following: in Romania, there is a short-run causality from money supply (M3) to GDP and a long-run relationship between GDP, internal credit and M3. According to Granger causality test, the rate of M3 in Romania was a cause for economic. In Czech Republic, there is a short-run causality from M3 to GDP and a long-run causality between GDP, internal credit and M3. Thus, the results contradict the money neutrality hypothesis in post-transformation Central European economies.